Determinación in vitro de la sensibilidad térmica de cepas de Xanthomonas axonopodis pv manihotis, agente causal de la bacteriosis vascular de la yuca - Ramírez, J.A.; Álvarez, E.; Marmolejo de la T., F (1999)
Cassava Bacterial Blight (CBB) is a destructive disease present in almost all the cassava-growing regions. CBB is caused by the bacteria Xanthomonas axonopodis pv. manihotis. If environmental conditions are favorable and control measures are not adopted, losses can reach 80% in only three crop cycles after incidence started. Furthermore, losses correlate with the number of infected cuttings used for planting. Heat treatment of planting material is a common technique used to control certain plant diseases. Thermotherapy inactivates or kills a pathogen while leaving the host tissue undamaged. In the present study, the thermal sensitivity of different X. axonopodis pv manihotis strains was established. Strains were collected in three edaphoclimatic zones (ECZ) in Colombia and one in Africa. Using a regression analysis, the ideal conditions for total growth inhibition were evaluated. In the same way, the growth development was assessed when changing the temperature and time of heat treatment. Using the results obtained we discussed the possibility of testing in vivo inhibition and the establishment of a protocol to clean the vegetative material using thermotherapy.